2013
DOI: 10.1037/a0032454
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic analysis of self-efficacy and perceived support: The relationship of individual and spousal characteristics with physical activity among middle-aged and young-older adults.

Abstract: The purpose of this study was to examine the associations among self-efficacy, perceived support, and physical activity in middle-aged and older married couples. A total of 116 middle-aged and older couples (M = 58.86 years, SD = 7.16, range 50-74) participated in the study. A dyadic approach to path modeling was taken. The final model indicated that for both husbands and wives, one's own self-efficacy was directly related to physical activity. In addition, husband self-efficacy was positively related to wive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Adjusting for self-efficacy strongly decreased the association between health literacy and physical activity. This is in line with some previous studies that suggested a pathway from health literacy to physical activity via self-efficacy and knowledge (Osborn et al, 2011), and that self-efficacy is directly associated with physical activity in older adults (Ayotte, Margrett, & Patrick, 2013). Self-efficacy was also suggested to mediate between health literacy and health behaviors in patients in a number of other studies (Bohanny et al, 2013;Osborn, Cavanaugh, Wallston, & Rothman, 2010;, but not all studies support this association (Chen et al, 2014;Colbert et al, 2013).…”
Section: Main Findingssupporting
confidence: 81%
“…Adjusting for self-efficacy strongly decreased the association between health literacy and physical activity. This is in line with some previous studies that suggested a pathway from health literacy to physical activity via self-efficacy and knowledge (Osborn et al, 2011), and that self-efficacy is directly associated with physical activity in older adults (Ayotte, Margrett, & Patrick, 2013). Self-efficacy was also suggested to mediate between health literacy and health behaviors in patients in a number of other studies (Bohanny et al, 2013;Osborn, Cavanaugh, Wallston, & Rothman, 2010;, but not all studies support this association (Chen et al, 2014;Colbert et al, 2013).…”
Section: Main Findingssupporting
confidence: 81%
“…Although other studies based on the APIM (Ayotte et al., ; Cook & Kenny, ) suggest that family support, general health status and depression may be correlated with PA or self‐efficacy for PA, none of these variables was significantly correlated. Individuals' PA was correlated with their own self‐efficacy and relative health status.…”
Section: Resultsmentioning
confidence: 66%
“…Ayotte et al. () reported no direct partner effects of family support on husbands' PA or wives' PA. Although we found only a one‐sided partner effect of friend support on PA, this result indicated that program designed to improve social support for PA might be helpful to promote friends' of participants' PA, not merely the participants' own PA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations